Intraoperative magnetic resonance imaging in epilepsy surgery: A systematic review and meta-analysis. (September 2021) - Englman, Cameron; Malpas, Charles B.; Harvey, A. Simon; Maixner, Wirginia J.; Yang, Joseph Yuan-Mou
Highlights: Forty-two intraoperative MRI (iMRI)-guided epilepsy surgery studies were reviewed. Studies contained heterogenous clinical characteristics and variable follow-up. Meta-analysis found iMRI led to higher gross total resection and seizure freedom rates. The results were undermined by moderate to significant statistical heterogeneity. There is, at best, level III-2 evidence supporting iMRI use in epilepsy surgery. Abstract: This systematic review investigated the added value of intraoperative magnetic resonance imaging (iMRI)-guidance in epilepsy surgery, compared to conventional non-iMRI surgery, with respect to the rate of gross total resection (GTR), postoperative seizure freedom, neurological deficits, non-neurological complications and reoperations. A comprehensive literature search was conducted using Medline, Embase, PubMed, and Cochrane Reviews databases. Randomized control trials, case control or cohort studies, and surgical case series published from January 1993 to February 2021 that reported on iMRI-guided epilepsy surgery outcomes for either adults or children were eligible for inclusion. Studies comparing iMRI-guided epilepsy surgery to non-iMRI surgery controls were selected for meta-analysis using random-effects models. Forty-two studies matched the selection criteria and were used for qualitative synthesis and ten of these were suitable for meta-analysis. Overall, studies included various 0.2–3.0 Tesla iMRI systems, contained small numbers with heterogenous clinical characteristics, utilized subjective GTR reporting, and had variable follow-up durations. Meta-analysis demonstrated that the use of iMRI-guidance led to statistically significant higher rates of GTR (RR = 1.31 [95% CI = 1.10–1.57]) and seizure freedom (RR = 1.44 [95% CI = 1.12–1.84]), but this was undermined by moderate to significant statistical heterogeneity between studies (I 2 = 55% and I 2 = 71% respectively). Currently, there is only level III-2 evidence supporting the use of iMRI-guidance over conventional non-iMRI epilepsy surgery, with respect to the studied outcomes.